Chondroitin sulfate disaccharide is a specific and sensitive biomarker for mucopolysaccharidosis type IVA. Issue 1 (30th June 2020) - Chin, Sharon J.; Saville, Jennifer T.; McDermott, Belinda K.; Zankl, Andreas; Fletcher, Janice M.; Fuller, Maria
Abstract: Mucopolysaccharidosis type IVA (MPS IVA) is an inborn error of glycosaminoglycan (GAG) catabolism characterized by a deficiency of the lysosomal enzyme, N ‐acetylgalactosamine 6‐sulphatase (GALNS). Consequently, partially degraded GAG, chondroitin 6‐sulfate (CS) and keratan sulfate (KS), accumulate in the lysosomes of affected cells, primarily in cartilage resulting in skeletal disease. Excessive urinary excretion of these GAG is often used as the initial biochemical parameter to inform a laboratory diagnosis. Here we present the utility of a CS‐disaccharide with a non‐reducing 6‐sulfated N ‐acetylgalactosamine residue (HNAc‐UA (1S))—the enzyme's substrate—for the diagnosis and biochemical monitoring of MPS IVA patients. Following implementation of this method into the diagnostic laboratory, we identified one MPS IVA patient over 3 years of MPS urine screening, with no false positive results from 2050 urines tested. Uniquely, urinary concentrations of HNAc‐UA (1S) are independent of age meaning that age‐related reference ranges are not required. Urinary HNAc‐UA (1S) was also able to identify two MPS IVA siblings who remained misdiagnosed with spondyloepiphyseal dysplasia for 5 years because of normal urinary GAG. HNAc‐UA (1S) could also be used as a biomarker for monitoring response to enzyme replacement therapy (ERT) as there was a drop in urinary concentration following the administration of ERT in all 12 patients and concentrations correlated with urinary KS ( R 2 = 0.92). In conclusion, HNAc‐UA (1S) is a reliable, sensitive and specific biomarker for the diagnosis of MPS IVA and can be used to biochemically monitor the response to ERT.